2012
DOI: 10.1242/dev.076760
|View full text |Cite
|
Sign up to set email alerts
|

Activated STAT regulates growth and induces competitive interactions independently of Myc, Yorkie, Wingless and ribosome biogenesis

Abstract: SUMMARYCell competition is a conserved mechanism that regulates organ size and shares properties with the early stages of cancer. In Drosophila, wing cells with increased Myc or with optimum ribosome function become supercompetitors that kill their wild-type neighbors (called losers) up to several cell diameters away. Here, we report that modulating STAT activity levels regulates competitor status. Cells lacking STAT become losers that are killed by neighboring wild-type cells. By contrast, cells with hyper-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
134
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 43 publications
12
134
1
Order By: Relevance
“…2 in Moreno et al, 2002), which is implicated in stress-induced apoptosis in Drosophila (Stronach and Perrimon, 1999). This finding has been confirmed by more recent work (Brumby and Richardson, 2003, Martin et al, 2009, Menendez et al, 2010, Tamori et al, 2010, although the involvement of JNK has not been demonstrated in some cases (de la Cova et al, 2004, Rodrigues et al, 2012, Tyler et al, 2007.…”
Section: Loser Cells Are Eliminated By Apoptosismentioning
confidence: 62%
“…2 in Moreno et al, 2002), which is implicated in stress-induced apoptosis in Drosophila (Stronach and Perrimon, 1999). This finding has been confirmed by more recent work (Brumby and Richardson, 2003, Martin et al, 2009, Menendez et al, 2010, Tamori et al, 2010, although the involvement of JNK has not been demonstrated in some cases (de la Cova et al, 2004, Rodrigues et al, 2012, Tyler et al, 2007.…”
Section: Loser Cells Are Eliminated By Apoptosismentioning
confidence: 62%
“…Additional factors have been implicated in cell competition, including other growth regulators 19 , cell polarity [34][35][36][37] and steep differences in signalling activity 14,38,39 (FIG. 2).…”
Section: Triggers Of Cell Competitionmentioning
confidence: 99%
“…Because of space constraints, here we do not discuss instances when steep differences in the activity of Wingless (which is the fly homologue of WNT), Decapentaplegic (Dpp; which is the fly homologue of transforming growth factor-β (TGFβ)) or JAK (Janus kinase)-STAT (signal transducer and activator of transcription) signalling trigger local apoptosis in a manner akin to cell competition 14,38,39 . Growth differential.…”
Section: Triggers Of Cell Competitionmentioning
confidence: 99%
“…9 Differences in Jak/Stat signaling, Wg signaling and cell adhesion are also reported to generate cell competition. [13][14][15] These findings suggest that cell competition arises from specific interactions between cells, rather than as a general consequence of differential growth.…”
mentioning
confidence: 90%